Research on Violence - Oblitas Béjar, Beatriz (2010)
Some of the problems of investigation on violence in our country, have to do with limitations on access to information, cooperation, funding and lack of knowledge of adequate procedures for collection and analysis of data. In order to make up for shortcomings in information, method, and bring us to the generation of a critical mass of researchers, two meetings on research on violence were organized. Individual and institutional researchers working in care and intervention in violence attended the first meeting. Consultation was done on access to financing sources, training requirements and suggestions for the organization of research into violence at the national level. The second meeting sought to strengthen the capacities of researchers on qualitative information and on Atlas Ti application for analysis of qualitative data.